Replacing Sugar Sweetened Beverages With Plain Water Improves Body Composition Among Female Youth - Nur Islami Mohd Fahmi Teng; Sa'ida Munira Johari; Nur Azma Amin; Hazwan Shah Ali; Siti Hajar Mukhtar; Norsham Juliana Nordin (Science and Education Publishing, 2024)
Indexing by ERA